A specific subpopulation of mesenchymal stromal cell carriers overrides melanoma resistance to an oncolytic adenovirus - Bolontrade, Marcela Fabiana (2012)
The homing properties of mesenchymal stromal c'ells (MSCs) toward tumors turn them into attractive tools for combining cell and gene therapy. The aim of this study was to select in a feasible way a human bone marrowderived MSC subpopulation that might exhibit a selective ability to target the tumor mass. Using differential in vitro adhesive capacities during cells isolation, we selected a specific MSC subpopulation (termed MO-MSCs) that exhibited enhanced multipotent capacity and increased cell surface expression of specific integrins (integrins a2, a3, and a5), which correlated with an enhanced MO-MSCs adhesiveness toward their specific ligands. Moreover, MO-MSCs exhibited a higher migration toward conditioned media from different cancer cell lines and fresh human breast cancer samples in the presence or not of a human microendothelium monolayer. Further in vivo studies demonstrated increased tumor homing of MO-MSCs toward established 578T and MD-MBA-231 breast cancer and A375N melanoma tumor xenografts. Tumor penetration by MO-MSCs was highly dependent on metallopeptidases production as it was inhibited by the specific inhibitor 1,10 phenantroline. Finally, systemically administered MO-MSCs preloaded with an oncolytic adenovirus significantly inhibited tumor growth in mice harboring established A375N melanomas, overcoming the natural resistance of the tumor to in situ administration of the oncolytic adenovirus. In summary, this work characterizes a novel MSC subpopulation with increased tumor homing capacity that can be used to transport therapeutic compounds.